Is too much a good thing? The non-linear relationship between intellectual capital and financial competitiveness in the Chinese automotive industry - Xu, Jian; Liu, Feng; Xie, Jingci (Journal of Business Economics and Management, 2022)
As one of the five largest industries in China, the automotive industry may well become a prosperous market of production and a large consumer market, but with the 2019 novel coronavirus (COVID-19) outbreak, automotive companies have suffered great losses. How to maintain financial competitiveness (FC) through innovation and knowledge after this calamity has become an area of focus for researchers and practitioners. By analyzing listed Chinese automotive companies over the period 2013–2018, the research focus is to determine the non-linear effect of intellectual capital (IC) on FC. IC is measured by the modified Value Added Intellectual Coefficient (MVAIC) model, and FC is measured through a comprehensive index system. The results reveal a cubic relationship between IC and FC. In addition, physical, innovation, and relational capitals have an S-shaped relationship with FC, whereas human capital has an inverted S-shaped curve. The non-linear effect of SC on FC is not significant. It is recommended that managers optimize investment in IC to drive FC in organizations.First published online 02 March 2022